2006
DOI: 10.1016/j.trstmh.2005.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Spleen enlargement and genetic diversity of Plasmodium falciparum infection in two ethnic groups with different malaria susceptibility in Mali, West Africa

Abstract: The high resistance to malaria in the nomadic Fulani population needs further understanding. The ability to cope with multiclonal Plasmodium falciparum infections was assessed in a cross-sectional survey in the Fulani and the Dogon, their sympatric ethnic group in Mali. The Fulani had lower parasite prevalence and densities and more prominent spleen enlargement. Spleen rates in children aged 2-9 years were 75% in the Fulani and 44% in the Dogon (P<0.001). There was no difference in number of P. falciparum geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 180 publications
(194 reference statements)
2
17
0
1
Order By: Relevance
“…The higher incidence of spleen enlargement in the Fulani might reflect a hyper immune reactivity of this secondary lymphoid organ (Bereczky et al, 2006;Vafa et al, 2009a;Alkadarou et al, 2013), a hypothesis supported by several studies which consistently show that the Fulani mount a more robust humoral immune response, as reflected by increased titers of anti-plasmodial antibodies (Modiano et al, 1998(Modiano et al, , 1999Bolad et al, 2005;Farouk et al, 2005a;Vafa et al, 2009a). The levels of malaria blood-stage antibodies anti-AMA1 and anti-MSP1 were significantly increased in Fulani, suggesting the higher specific humoral responses against AMA1 and MSP1 in this ethnic group (Dolo et al, 2012a).…”
Section: Identification Of the Immune Mechanisms Of Resistance To Malmentioning
confidence: 95%
See 1 more Smart Citation
“…The higher incidence of spleen enlargement in the Fulani might reflect a hyper immune reactivity of this secondary lymphoid organ (Bereczky et al, 2006;Vafa et al, 2009a;Alkadarou et al, 2013), a hypothesis supported by several studies which consistently show that the Fulani mount a more robust humoral immune response, as reflected by increased titers of anti-plasmodial antibodies (Modiano et al, 1998(Modiano et al, , 1999Bolad et al, 2005;Farouk et al, 2005a;Vafa et al, 2009a). The levels of malaria blood-stage antibodies anti-AMA1 and anti-MSP1 were significantly increased in Fulani, suggesting the higher specific humoral responses against AMA1 and MSP1 in this ethnic group (Dolo et al, 2012a).…”
Section: Identification Of the Immune Mechanisms Of Resistance To Malmentioning
confidence: 95%
“…Several studies have demonstrated that the Fulani are less parasitized, have a higher incidence of spleen enlargement (Bereczky et al, 2006) and are less affected by malaria sickness, despite the fact that people in these areas are exposed to malaria at the same level. Moreover, it has been observed that the pyrogenic threshold of parasitemia was 1,000 parasites/l of blood in the Dogon and 5,000 parasites/l of blood in the Fulani (Dolo et al, 2012b) and that the Fulani present more often with symptoms of anemia than the Dogon, despite their lower susceptibility to malaria (Dolo et al, 2012c).…”
Section: Clinical and Parasitological Evidence Of Interethnic Differementioning
confidence: 99%
“…Splenomegaly is a characteristic of malaria infections, observed in human infections and rodent models [17-19]. In mice, this is thought to be due in part to the haematopoetic response to the high numbers of RBC lost through infection, and to the trapping of leukocytes in the spleen [20-23].…”
Section: Discussionmentioning
confidence: 99%
“…Si la SPH est avant tout secondaire à une infection à P. falciparum, elle ne semble pas liée à des souches plasmodiales particulières au sein de cette espèce [8].…”
Section: éLéments De Physiopathologieunclassified